2022
DOI: 10.3389/fmicb.2022.715637
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Ecological Diversity in Acidobacteria

Abstract: Acidobacteria occur in a large variety of ecosystems worldwide and are particularly abundant and highly diverse in soils. In spite of their diversity, only few species have been characterized to date which makes Acidobacteria one of the most poorly understood phyla among the domain Bacteria. We used a culture-independent niche modeling approach to elucidate ecological adaptations and their evolution for 4,154 operational taxonomic units (OTUs) of Acidobacteria across 150 different, comprehensively characterize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Structural equation models confirmed a positive direct effect of increased richness of Acidobacteria and Firmicutes on cropland productivity, while the opposite was observed for Chytridiomycota (i.e., increased OTU richness led to lower productivity). Acidobacteria are abundant soil-borne microorganisms known to be involved in nutrient mineralization and organic matter degradation (Banerjee et al, 2016; Kielak et al, 2016; Sikorski et al, 2022). Our results also align with a recent study where Acidobacteria positively correlated with cropland productivity in a four-decade fertilization experiment (Fan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Structural equation models confirmed a positive direct effect of increased richness of Acidobacteria and Firmicutes on cropland productivity, while the opposite was observed for Chytridiomycota (i.e., increased OTU richness led to lower productivity). Acidobacteria are abundant soil-borne microorganisms known to be involved in nutrient mineralization and organic matter degradation (Banerjee et al, 2016; Kielak et al, 2016; Sikorski et al, 2022). Our results also align with a recent study where Acidobacteria positively correlated with cropland productivity in a four-decade fertilization experiment (Fan et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Predictor ranking based on relative importance following multi-model averaging indicated that the best predictor of primary productivity in croplands was the richness of Acidobacteria (Figure 4). Acidobacteria are abundant soil-borne microorganisms known to be involved in nutrient mineralization and organic matter degradation (Banerjee et al, 2016; Kielak et al, 2016; Sikorski et al, 2022). Here we demonstrate for the first time that the positive effect of Acidobacteria on primary productivity is comparatively higher in croplands than in woodlands or grasslands (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…These were taxa that were more abundant in native soils, and also more abundant on native genotypes when grown in the invaded soils in which these same groups were more depauperate (again suggesting preferential accumulation). These groups have a variety of potential functions of interest, and include an uncultured Gaiellales family (a group that has been associated with plant colonizers, and may regulate organic and fatty acids in soils (Ye et al 2021; L. Sun et al 2022)); a family in Subgroup 1 of the Acidobacteriaceae (a diverse group of oligotrophs abundant in soils, some of which have adapted to specific dry soil conditions; (Kielak et al 2016; Sikorski et al 2022)), a family in the CPla-3 termite group (a more highly specialized group in the soil, often in acidic environments; (Fickling et al 2024)), and the family Polyangiaceae (a group of predatory social bacteria, among the most common predators of bacteria in the soil, with the potential to structure the diversity of the entire microbial community (Petters et al 2021; Z. Wu et al 2022; Thakur and Geisen 2019)).…”
Section: Discussionmentioning
confidence: 99%
“…Soil texture was determined by the sieve‐pipette method, SOM was removed by oxidation with hydrogen peroxide, in which soil aggregates were dispersed. Afterwards, the sand (2–0.02 mm), silt (0.02–0.002 mm) and clay (<0.002 mm) fractions were determined by sieving and sedimentation (Sikorski et al, 2022).…”
Section: Methodsmentioning
confidence: 99%